Scaling Static Analyses at Facebook. - DISTEFANO, DINO; FÄHNDRICH, MANUEL; LOGOZZO, FRANCESCO; O'HEARN, PETER W. (Communications of the ACM, 2019)
The article discusses the use of static analysis techniques by the social media firm Facebook Inc. Topics include the use of deep reasoning in relation to source code, the importance of catching software bugs in the use of static analysis, and the use of the tool Infer in relation to continuous software development practices used by Facebook.